Information and cervical screening: a qualitative study of women's awareness, understanding and information needs about HPV. - Goldsmith, MR; Bankhead, C; Kehoe, S; Marsh, G; Austoker, J (2007)
OBJECTIVES: To explore women's attitudes towards the information about human papilloma virus (HPV) provided during cervical screening and to describe women's HPV information needs. SETTING: Women with a range of screening results (normal, inadequate, borderline and abnormal) were identified by three screening centres in England. Two consecutive samples of women attending for colposcopy for the first time following screening were also approached. METHODS: Seven focus groups were conducted between May 2005 and April 2006 with 38 women who had recently been for cervical screening or had attended a colposcopy appointment. RESULTS: Most women had no prior awareness of HPV. Many women queried the importance of being informed about HPV as no preventive advice or treatment is available. The HPV information included in the UK national screening programme abnormal result leaflet left women with more questions than answers (a list of unanswered questions is included with the results). Further information was requested about HPV detection, infection and transmission as well as the natural history and progression of cervical cancer. No consensus was reached regarding the best time to provide HPV information. CONCLUSIONS: Clear communication of the complicated issues surrounding HPV infection and the natural history of cervical cancer is a considerable educational challenge for screening providers. As awareness of HPV becomes more widespread and HPV testing is explored as a triage during cervical screening, women are likely to require more information about the virus and the implications of infection. Consideration should be given to the production of a separate national screening programme HPV leaflet.